Are South Africa's National Development Plan's economic growth and employment initiatives sufficiently robust to realise vision 2030? A cross-country analysis. - Saville, Adrian (University of Pretoria, 2018)
Mini Dissertation (MBA)--University of Pretoria, 2017.